The Discourse of Imunity Maintenance in Hindu Tradition of Samkhya-Yoga and Usadha - I Wayan Suka Yasa; W. A. Sindhu Gitananda; I Nyoman Sridana (International Journal of Interreligious and Intercultural Studies, 2022)
According to Hinduism, especially the Samkhya-Yoga system, viruses, bacteria and other microscopic creatures are classifid as external diseases (adibhautika duhka) which cause such severe illness as Covid-19 so as found in the Usadha in different terms. This paper aims at understanding the discourse of imunity maintenance in Hindu tradition, especially those implied by the Samkhya-Yoga sistem of philosophy and Usadha Bali. Within the concept of both systems, it is found that the life and health means having knowledge (pramana) with the peak of viveka‘discriminative knoledge of dualism’, siddhi, and sakti. The life is not due to being into death, yet rather meaning having been the process of returning to the root cause of life. Having elaborated the data, the discourse of the imunity maintenance may be implied within the concept of sadhana telu: jnana bhyudreka ‘knowledge of tattwa’, indriya yoga marga ‘mistical sense practice of yoga’ and trsna dosa ksaya ‘diminishing all the will or dosa’. Therefore, the Samkhya-Yoga and Usadha serves to harmonize the physical, mental and spiritual through certain practices of yoga.